Corrosion behaviour of the 2098-T351 Al–Cu–Li alloy after different surface treatments. (3rd April 2022) - das Graças Barboza, Wanessa; Xavier Milagre, Mariana; Donatus, Uyime; de Souza Carvalho Machado, Caruline; Prada Ramirez, Oscar Mauricio; de Sousa Araujo, João Victor; da Silva, Rejane Maria Pereira; Costa, Isolda
ABSTRACT: The effect of different surface treatments on the corrosion resistance of the AA2098 Al–Cu–Li alloy has been investigated. Surface characterization was performed using 3D optical profilometry, energy dispersive X-ray spectroscopy and scanning electron microscopy. The corrosion resistance of the 2098 alloy after the surface treatments was investigated in 0.1 mol L −1 NaCl solution by electrochemical techniques and microscopy. Corrosion results showed that the untreated and the chemically etched surfaces were more active than the mechanically abraded and mechanically polished surfaces owing to differences in the nature of the native oxides formed after the surface treatments. Corrosion rate and mode were also affected by how close the exposed surface was to the mid-thickness region of the AA2098-T351 plate relative to the actual top surface (before polishing). This is associated with the variation in the volume fraction and distribution of the T1 phase as the mid-thickness region of the AA2098-T351 plate is approached.